A Hybrid Heuristic Algorithm to Enhance Load balancing in Cloud Environment - Ravi Teja Kanakala, V; Pavan Kumar, K; Kavitha, S (International Journal of Computer Sciences and Engineering, 2025)
Cloud computing, an internet based technology which provides virtualized computer resources over the internet. Distribution of the dynamic workload among the computer resources in the cloud evenly in such a way that no single node is overloaded or under loaded is called Load Balancing. An efficient load balancer will increase the performance of cloud, maximizes the cloud services and also increases the resource utilization. Today increasing the performance of a cloud depends on many factors, among them Load Balancing is one of the main factors. In this paper we propose a load balancing algorithm which is a variant to the Weight Least Connection (WLC) algorithm. The proposed algorithm shows better results in several aspects like accurate calculation of work load on a resource, distributing the work load on the service nodes efficiently, enhancing the response time and minimizing the overall task execution time.